If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -10(7 + m) = -230 (7 * -10 + m * -10) = -230 (-70 + -10m) = -230 Solving -70 + -10m = -230 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '70' to each side of the equation. -70 + 70 + -10m = -230 + 70 Combine like terms: -70 + 70 = 0 0 + -10m = -230 + 70 -10m = -230 + 70 Combine like terms: -230 + 70 = -160 -10m = -160 Divide each side by '-10'. m = 16 Simplifying m = 16
| 34.5=(2)(3.14)(x) | | 1.1x+1.2x-5.4=-16 | | -7n=-98 | | p^2+p=x | | 59.7=(2)(3.14)(x) | | 8-6a=4(a-3) | | -1.333333+y+y=3 | | 3120=(26000)(0.03)(x) | | 0=12-5x+3y | | ax-r=12 | | 4(6p-8)=24p-23 | | 15r=60 | | 43z-1=4(13z-16) | | -10x+9x=-9+10 | | 1.43x(-19/37)= | | -4z-4z=3z+3+3z | | 30-10k=22-2k | | 7=12z+18-5 | | Y=yz+10 | | -8(-8x-6)=-6x-222 | | s+7(4)=16 | | 193=3+10p | | -3(-3+y)+3y=4 | | -5m=-85 | | -7(x+4)=0 | | 6n-2(3-n)=-13 | | 44+2c=7c-6 | | x/13=-7 | | 3x+3/3= | | 6(2m-1)-1(11m+6)=7 | | 7x-11=17-7x | | 60-2m=8m |